Rapid transition from in‐person to videoconferencing psychotherapy in a counselor training clinic: A safety and feasibility study during the COVID‐19 pandemic. (18th May 2022) - Hall, Sean B.; Bartley, Alise G.; Wenk, Julieta; Connor, Annemarie; Dugger, Suzanne M.; Casazza, Krista
Abstract: Due to the COVID‐19 pandemic, many counselor training clinics rapidly transitioned in‐person (IP) services to videoconferencing psychotherapy (VCP). Because VCP is a relatively new technology, more research is needed to establish whether this delivery format is a safe and acceptable substitute for IP services in counselor training clinics. The purpose of this study is to explore questions related to how clients perceive VCP versus IP in terms of credibility and expectancy. Results from this investigation demonstrate that clients who participate in VCP, without first meeting their counselor in person, may initially question the credibility and effectiveness of VCP. However, results demonstrated improvement, in both groups, across the duration of therapy. These findings provide both initial support for the safety of VCP in counselor training clinics and justification for further research.